SNAP Decisions: Qualitative Research on the Perceived Influence of the COVID-19 Pandemic and Supplemental Nutrition Assistance Program Benefit Changes on Food Purchases - C. Ross Hatton; Jessica Eller; Denise Simon; Melanie Caldwell; Alexandra Ross; Anne N. Thorndike; Eric B. Rimm; Joshua Petimar; Michele Polacsek (Journal of the Academy of Nutrition and Dietetics, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Towards new horizons in shrimp cell culture: A streamlined protocol for culturing healthy, enduring haemocytes and lymphoid organ cells from Pacific whiteleg shrimp (Litopenaeus vannamei) - Alexandra Florea; Sarah Ho; Joe Mee; Ross Houston; Diego Robledo; Tim P. Bean (Aquaculture, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Genetic signatures of bufadienolide resistance are poor predictors of cane toad toxin resistance in crocodilians - Alexandra K. Ross; Pierre Ibri; Jonathan K. Webb; Tim S. Jessop; Tim Dempster; Charlotte H. Mills; Tahneal Hawke; Mike Letnic; Stephen Frankenberg (Evolutionary Ecology, 2026)

Understanding Motivators and Challenges to Enrollment in Maternal and Child Health and Nutrition Research: A Mixed Methods Study with Women of Child-Bearing Age and Clinical Practitioners - Alexandra MacMillan Uribe; Rebecca Seguin Fowler; Kelly Fisher; Erica Bender; Galen Eldridge; Margaret Demment; Regan Bailey; A. Catharine Ross; Diane Mitchell; Sarah Ray; Julie Gras-Najjar; Alexandra Early (Journal of Nutrition Education and Behavior, 2025)

Heat-tolerant algal symbionts may prevent extirpation of the threatened elkhorn coral, Acropora palmata, in Florida during intensifying marine heatwaves - Richard F. Karp; Fabrizio Lepiz-Conejo; Shayle B. Matsuda; Bryce Corbett; Alexandra D. Wen; Joseph D. Unsworth; Martine D’Alessandro; Ken Nedimyer; Amelia Moura; Erinn M. Muller; Zachary Craig; Diego Lirman; et al. (Coral Reefs, 2025)
The elkhorn coral, Acropora palmata , was historically a major reef-building species in the Caribbean, but has suffered devastating declines in recent decades. Despite significant restoration efforts in Florida, the marine heatwave of 2023 caused severe bleaching and mortality to both wild and restored colonies. To understand the disastrous impacts, we evaluated the variation in heat tolerance among Florida’s A. palmata population prior to the event. In 2022, we used rapid acute heat stress assays to assess the thermal tolerance of 172 adult colonies (125 unique genets) from four nurseries. We found variation in thermal tolerance (4.17°C range in ED50) that was attributed to nursery location (17.2% of variation), genet (25.9%), and symbiont abundance (15.6%). Algal symbiont type, however, was the strongest predictor of thermal performance, with the few (n = 10) colonies hosting Durusdinium being, on average, 1.9°C more thermally tolerant than corals hosting Symbiodinium . This difference would have decreased the effective heat stress accumulation during the 2023 event by ~92%. Therefore, despite considerable variation in thermal tolerance among Florida’s elkhorn corals, hosting Durusdinium appears to be the most effective mechanism for surviving such extreme heat stress. These findings suggest that restoration strategies that focus on rearing sexually derived A. palmata recruits with Durusdinium , followed by outplanting to suitable environments, may improve survival during future heatwaves. Combined with efforts to introduce additional elkhorn diversity from populations outside Florida, these approaches may be the most effective interventions to promote the continued survival of Florida’s elkhorn corals in the face of rapid climate change.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

A review of policy levers to reduce meat production and consumption - Christopher Bryant; Abby Couture; Euan Ross; Alexandra Clark; Tom Chapman (Appetite, 2024)

Emerging mosquitoes (Aedes nigripes) as a resource subsidy for wolf spiders (Pardosa glacialis) in western Greenland - Lauren E. Culler; Alexandra M. Stendahl; Melissa H. DeSiervo; Hanna M. Bliska; Ross A. Virginia; Matthew P. Ayres (Polar Biology, 2024)

‘Perverse outcomes’ or premature interpretation: Response to , “Loss of antipredator traits in a havened mammal population.” - John Kanowski; Jennifer Anson; Amanda Bourne; Bryony Palmer; Jennifer Pierson; Alexandra Ross (Biological Conservation, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Effects of Infectious Diseases on Population Dynamics of Marine Organisms in Chesapeake Bay - Jerelle A. Jesse; M. Victoria Agnew; Kohma Arai; C. Taylor Armstrong; Shannon M. Hood; Mariah L. Kachmar; Jessie T. Long; Alexandra J. McCarty; Morgan O. Ross; Kasondra D. Rubalcava; Jacob Shaner; Sakura Tanaka; et al. (Estuaries and Coasts, 2021)
Diseases are important drivers of population and ecosystem dynamics. This review synthesizes the effects of infectious diseases on the population dynamics of nine species of marine organisms in the Chesapeake Bay. Diseases generally caused increases in mortality and decreases in growth and reproduction. Effects of diseases on eastern oyster ( Crassostrea virginica ) appear to be low in the 2000s compared to effects in the 1980s–1990s. However, the effects of disease were not well monitored for most of the diseases in marine organisms of the Chesapeake Bay, and few studies considered effects on growth and reproduction. Climate change and other anthropogenic effects are expected to alter host-pathogen dynamics, with diseases of some species expected to worsen under predicted future conditions (e.g., increased temperature). Additional study of disease prevalence, drivers of disease, and effects on population dynamics could improve fisheries management and forecasting of climate change effects on marine organisms in the Chesapeake Bay.

The Prospect of Global Coral Reef Bathymetry by Combining Ice, Cloud, and Land Elevation Satellite-2 Altimetry With Multispectral Satellite Imagery - Arthur C. R. Gleason; Ross Smith; Sam J. Purkis; Kyle Goodrich; Alexandra Dempsey; Alejandro Mantero (Frontiers in Marine Science, 2021)
Empirical methods for estimating shallow-water bathymetry using passive multispectral satellite imagery are robust and globally applicable, in theory, but they require copious local measurements of water depth for algorithm calibration. Such calibration data have historically been unavailable for most locations, but NASA’s Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2), a satellite-based LiDAR, might hold unique promise to fill this critical data gap. Although ICESat-2 was not designed as a marine altimeter, its ATLAS sensor consists of six green (532 nm) lasers that can penetrate a water surface and return photons reflected by the seabed, thereby generating bathymetric profiles. Utilizing TCarta’s NSF SBIR-funded Space-Based Laser Bathymetry Extraction Tool and ICESat-2’s ATL03 geolocated photon data product, we have compared ICESat-2 bathymetric retrievals with a portfolio of soundings acquired in situ using a vessel-mounted single-beam echosounder. This analysis demonstrated very high correlation ( R 2 = 0.96) between the field and space-based bathymetry data. The comparisons were made at multiple Caribbean and Pacific coral reef sites over water depths ranging from 1 to 20 m. Results suggest that ICESat-2 could be an effective approach for calibrating and validating empirical and radiative transfer methods, alike, for estimating shallow-water bathymetry from remote sensing imagery, thereby enabling the immediate potential for shallow-water bathymetric mapping of Earth’s reefs.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Correction to: Formation by silicate–fluoride + phosphate melt immiscibility of REE-rich globular segregations within aplite dikes - Charles R. Stern; Julien M. Allaz; Markus B. Raschke; G. Lang Farmer; M. Alexandra Skewes; Jeremy T. Ross (Contributions to Mineralogy and Petrology, 2018)

From Jumbo to Dumbo: Cranial Shape Changes in Elephants and Hippos During Phyletic Dwarfing - Alexandra A. E. van der Geer; George A. Lyras; Philipp Mitteroecker; Ross D. E. MacPhee (Evolutionary Biology, 2018)

Formation by silicate–fluoride + phosphate melt immiscibility of REE-rich globular segregations within aplite dikes - Charles R. Stern; Julien M. Allaz; Markus B. Raschke; G. Lang Farmer; M. Alexandra Skewes; Jeremy T. Ross (Contributions to Mineralogy and Petrology, 2018)

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

California forests show early indications of both range shifts and local persistence under climate change - Josep M. Serra‐Diaz; Janet Franklin; Whalen W. Dillon; Alexandra D. Syphard; Frank W. Davis; Ross K. Meentemeyer (Global Ecology and Biogeography, 2016)
Aim Forest regeneration data provide an early signal of the persistence and migration of tree species, so we investigated whether species shifts due to climate change exhibit a common signal of response or whether changes vary by species. Location California Floristic Province, United States ; mediterranean biome. Methods We related Forest Inventory and Analysis ( FIA ) data from 2000−07 for 13 tree species to high‐resolution climate and geographical data. Using methods from invasion ecology, we derived indices of species‐specific regeneration overlap and central tendency change (range‐wide global indicators) based on kernel density estimation of presence and absence of regeneration. We then built regeneration surfaces to identify areas of occurrence of high regeneration (regeneration hotspots, local indicators) in both geographical and climate space for 13 common tree species. Results Differences between presence and absence of regeneration in forests varied in magnitude across species, with little evidence that tree regeneration is shifting to higher latitudes and elevations, the expected geographical fingerprint of climate change. We also identified potential topographic mediators of regeneration dynamics. Multiple regeneration hotspots were found for many species, suggesting the influence of non‐climatic factors on regeneration. Differences between the presence and absence of regeneration in geographic and climate spaces were not always congruent, suggesting that shifting climate space and range area are not entirely coupled. Main conclusions The distributions of regeneration in Californian forests show diverse signals, not always tracking the higher latitudinal–elevation fingerprint of climate change. Local regeneration hotspots are common in our analysis, suggesting spatially varying persistence of forest linked to natural and anthropogenic disturbances. Our results emphasize that projections of tree range shifts in the context of climate change should consider the variation of regeneration drivers within species ranges, beyond the overall climate signal.

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism - Alexandra C. G. Thomson; Paul H. York; Timothy M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2015)

Evolutionary refugia and ecological refuges: key concepts for conserving Australian arid zone freshwater biodiversity under climate change - Jenny Davis; Alexandra Pavlova; Ross Thompson; Paul Sunnucks (Global Change Biology, 2013)
Refugia have been suggested as priority sites for conservation under climate change because of their ability to facilitate survival of biota under adverse conditions. Here, we review the likely role of refugial habitats in conserving freshwater biota in arid Australian aquatic systems where the major long‐term climatic influence has been aridification. We introduce a conceptual model that characterizes evolutionary refugia and ecological refuges based on our review of the attributes of aquatic habitats and freshwater taxa (fishes and aquatic invertebrates) in arid Australia. We also identify methods of recognizing likely future refugia and approaches to assessing the vulnerability of arid‐adapted freshwater biota to a warming and drying climate. Evolutionary refugia in arid areas are characterized as permanent, groundwater‐dependent habitats (subterranean aquifers and springs) supporting vicariant relicts and short‐range endemics. Ecological refuges can vary across space and time, depending on the dispersal abilities of aquatic taxa and the geographical proximity and hydrological connectivity of aquatic habitats. The most important are the perennial waterbodies (both groundwater and surface water fed) that support obligate aquatic organisms. These species will persist where suitable habitats are available and dispersal pathways are maintained. For very mobile species (invertebrates with an aerial dispersal phase) evolutionary refugia may also act as ecological refuges. Evolutionary refugia are likely future refugia because their water source (groundwater) is decoupled from local precipitation. However, their biota is extremely vulnerable to changes in local conditions because population extinction risks cannot be abated by the dispersal of individuals from other sites. Conservation planning must incorporate a high level of protection for aquifers that support refugial sites. Ecological refuges are vulnerable to changes in regional climate because they have little thermal or hydrological buffering. Accordingly, conservation planning must focus on maintaining meta‐population processes, especially through dynamic connectivity between aquatic habitats at a landscape scale.

Global patterns in the impact of marine herbivores on benthic primary producers - Alistair G. B. Poore; Alexandra H. Campbell; Ross A. Coleman; Graham J. Edgar; Veijo Jormalainen; Pamela L. Reynolds; Erik E. Sotka; John J. Stachowicz; Richard B. Taylor; Mathew A. Vanderklift; J. Emmett Duffy (Ecology Letters, 2012)
Despite the importance of consumers in structuring communities, and the widespread assumption that consumption is strongest at low latitudes, empirical tests for global scale patterns in the magnitude of consumer impacts are limited. In marine systems, the long tradition of experimentally excluding herbivores in their natural environments allows consumer impacts to be quantified on global scales using consistent methodology. We present a quantitative synthesis of 613 marine herbivore exclusion experiments to test the influence of consumer traits, producer traits and the environment on the strength of herbivore impacts on benthic producers. Across the globe, marine herbivores profoundly reduced producer abundance (by 68% on average), with strongest effects in rocky intertidal habitats and the weakest effects on habitats dominated by vascular plants. Unexpectedly, we found little or no influence of latitude or mean annual water temperature. Instead, herbivore impacts differed most consistently among producer taxonomic and morphological groups. Our results show that grazing impacts on plant abundance are better predicted by producer traits than by large‐scale variation in habitat or mean temperature, and that there is a previously unrecognised degree of phylogenetic conservatism in producer susceptibility to consumption.

Inactivation status of PCDH11X: sexual dimorphisms in gene expression levels in brain - Alexandra M. Lopes; Norman Ross; James Close; Adam Dagnall; António Amorim; Timothy J. Crow (Human Genetics, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

The measurement of water activity in allogeneic skin grafts preserved using high concentration glycerol or propylene glycol - Alexandra Ross; John N. Kearney (Cell and Tissue Banking, 2004)

A single nucleotide polymorphism (SNP) in the leptin receptor is associated with BMI, fat mass and leptin levels in postmenopausal Caucasian women - Naomi Quinton; Allison Lee; Richard Ross; Richard Eastell; Alexandra Blakemore (Human Genetics, 2001)